2009
DOI: 10.3238/arztebl.2009.0175
|View full text |Cite
|
Sign up to set email alerts
|

Prostatitis and Male Pelvic Pain Syndrome

Abstract: The prostatitis syndrome is a complex condition with a tendency toward chronification. It is important, therefore, that the patient be fully informed about the diagnostic uncertainties and the possibility that treatment may meet with less than complete success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 40 publications
0
30
0
14
Order By: Relevance
“…A recent review article summarizing the results of six chronic bacterial prostatitis studies showed that ciprofloxacin, administered as a single agent at a dose of 1 g day 21 for 4 weeks, results in eradication rates ranging between 63% and 77%. 42 The present study shows that in chronic bacterial prostatitis, the daily dosage of the fluoroquinolone is more crucial than the duration of therapy, as administration of the cumulative dose of 21 g of ciprofloxacin at the rate of 750 mg day 21 for 4 weeks, rather than 500 mg day 21 for 6 weeks, increased eradication rates from 62.35% to 77.32% and the total bacteriological success from 71.76% to 85.57%. In particular, increased eradication of Enterococci was observed in the Cipro-750 cohort.…”
Section: Discussionmentioning
confidence: 59%
“…A recent review article summarizing the results of six chronic bacterial prostatitis studies showed that ciprofloxacin, administered as a single agent at a dose of 1 g day 21 for 4 weeks, results in eradication rates ranging between 63% and 77%. 42 The present study shows that in chronic bacterial prostatitis, the daily dosage of the fluoroquinolone is more crucial than the duration of therapy, as administration of the cumulative dose of 21 g of ciprofloxacin at the rate of 750 mg day 21 for 4 weeks, rather than 500 mg day 21 for 6 weeks, increased eradication rates from 62.35% to 77.32% and the total bacteriological success from 71.76% to 85.57%. In particular, increased eradication of Enterococci was observed in the Cipro-750 cohort.…”
Section: Discussionmentioning
confidence: 59%
“…Finalmente, la muestra Nº 4 corresponde a los primeros 10 ml de volumen evacuado posterior al masaje. Este especimen probablemente incluye la secreción prostática que permanece en la uretra después del masaje (7,8) .…”
Section: Discussionunclassified
“…Chronic prostatitis/chronic pelvic pain syndrome (CP/ CPPS, NIH category III), is the most prevalent form of prostatitis, which is characterized by chronic pelvic pain without an infection of the urinary tract [1][2][3][4][5]. To date, the pathogenesis of CP/CPPS is also unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the pathogenesis of CP/CPPS is also unclear. Five different causes, including infection, detrusor-sphincter dysfunction, immunological dysfunction, interstitial cystitis and neuropathic pain, have been discussed [3,4]. According to the presence or absence of inflammatory cells in the expressed prostatic secretions (ePS), CP/CPPS is split into inflammatory CP/CPPS (category IIIa) and non-inflammatory CP/CPPS (IIIb).…”
Section: Introductionmentioning
confidence: 99%